Length-weight relationship of Sufflamen fraenatus (Latreille, 1804) and Zenodon niger (Ruppell, 1835) - Sahayak, Satish (Indian Journal of Fisheries, 2011)
The relationship between total length and total weight in balistids is notsignificantly different in males and females. The common equation for boththe sexes in Sufflamen fraenatus isLog W= -9.0429+2.7296 log L or W=0.000000000905* L 2.7296,R2 = 0.9301,and in Zenodon niger isLog W= -6.507+2.085 log L or W=0.0000003117* L2.08556R2 = 0.6749.